O absurdo da existência nos contos de Murilo Rubião - Sardas, Guilherme (2014)
Many short stories of Murilo Rubião (1916-1991) bring actions and situations generally perceived as absurd, which analyzed thoroughly, can be considered representations of the feeling of estrangement of man in the world and the emptying of meaning of modern experience. The critics often associate the fantastic typical of the author to the category of absurd. But what characterizes the absurd universe created by Rubião? This research aims to investigate the construction of the absurd in work of Rubião, both thematically and discursive. The theoretical basis for this work is the absurd philosophy, present in the essay The myth of Sisyphus, by Albert Camus, and some ideas and concepts of Jean-Paul Sartre s existentialism. Considering this, we seek to demonstrate how is the dialogue between the short stories of Rubião and the absurd according thoughts of these philosophers of existence. Parallel to the study of this theme on construction of the absurd by Rubião, will seek to analyze the use of the tools of language to create this absurdity or, in other words, the creation of a poetic of the absurd in writing of the author. While the absurdity of Rubião dialogues with ideas of the philosophy of existence, it has also important differences in some points of the dramatic content of existential and existentialist literature, presenting ironic, comic and fantastic forms. Analyze how Murilo Rubião demarcates the peculiarities of its absurdity and the relations of this absurdity with the procedures of the modern fantastic are also motivations of this research